المعاملات التجارية للموانئ - بن محال, موسى (My University, 2023)
The foreign trade sector in the port of Mostaganem is one of the most vital sectors in the Algerian economy, and some Algerian economists saw that foreign trade contributes to achieving economic growth, especially from the import side. It is advanced in development, and indeed no country can live in isolation from the world by working to achieve an economic balance, working to reduce imports, especially consumer ones, and working to promote exports to advance the economy and keep abreast of international trade developments, and this is what Algeria seeks today to achieve through its ports, especially the port Mostaganem, as well as the development of its commercial transactions and access to a degree that promotes it to the forums of the major ports
دراسة ميدانية في ميناء مستغانم
Keywords: Port of Mostaganem, import, imports, development of commercial transactions, ports